ChemInform Abstract: Self‐Assembly of Proteins: Towards Supramolecular Materials. Issue 51 (5th December 2016) - Yang, Liulin; Liu, Aijie; Cao, Shuqin; Putri, Rindia M.; Jonkheijm, Pascal; Cornelissen, Jeroen J. L. M.
Abstract: Review: 80 refs.